Financial Sustainability of Selected MFIs of Nepal - Sharma, Puspa Raj (Journal of Nepalese Business Studies, 2009)
This paper aims to analyze the financial sustainability of selected MFIs. In this regard, it deals with concept of sustainability, financial sustainability including operational and financial self-sufficiency. It also deals operating performance, staff productivity, portfolio quality and relation of financial sustainability with other variables. Nepalese MFIs are not strong from status of sustainability perspective at present. PI-MFIs are in better position than GI-MFIs. The data had collected from a special survey carried out in hill and terai in 2004-2006 of Nepal. Key Words: Sustainability, financial, operating, MFIs. The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page:24-36